Internet browser bookmark synchronization tool / Muhd Baharul Nashim Ibrahim - Ibrahim, Muhd Baharul Nashim (Faculty of Computer and Mathematical Sciences, 2007)
Synchronization is a process balancing two or more places. Synchronization can be applied to many applications such as hand phone, PDA and others. This research is focus on Mozilla Firefox browser bookmark. The name of the tool that wants to develop is Internet Browser Bookmark Synchronization Tool. The tool is function to synchronize user bookmark and more specifically synchronize the Uniform Resource Locator (URL) in the bookmark file. Currently, there are several bookmark synchronizer tool available nowadays. But it is a package that should be installed on the browser or in other word is the extension of the browser. Current tool require connection between pc to pc and internet connection. The develop tool is not require those connection, it can be done by copying the file and insert into the tool. Objective if this research is to identify the file management technique especially synchronization technique, to identify and compare the current available bookmark synchronization method and tool and to design and test the bookmark synchronization tool for browser. Literature review is consist all the information related to research field, it will explain clearly on synchronization, file synchronization and others related to bookmark synchronization. All the reading materials is categories as secondary data, primary data is more on exploration study which is include making experiment on available bookmark such as making comparison. As the result of the experiment it will tell clearly the strength and the weaknesses of the tools and also the structure of the tools. After get clear view from the experiment, process developing the tool using Java language will become easy.